One wrong move [large type] - Pettrey, Dani (Jeopardy Falls, 2024)
"Christian O'Brady was pulled into a life of crime at a young age by his con artist parents. Now making amends for his corrupt past, he has become one of the country's foremost security experts. When a string of Southwestern art heists targets one of the galleries Christian secured, he is paired up with a gifted insurance investigator who has her own checkered past. Andi Forester was a brilliant FBI forensic analyst until one of her colleagues destroyed her career, blaming her for mishandling evidence. She now puts those skills to work investigating insurance fraud, and this latest high-stakes case will test her gift to the limit. Drawn deep into a dangerous game with an opponent bent on revenge, Christian and Andi are in a race against the clock to catch him, but the perpetrator's game is far from finished, and one wrong move could be the death of them both."--